Technological interdependencies and employment changes in European industries - Lorenzo Cresti; Giovanni Dosi; Giorgio Fagiolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This work addresses the role of inter-sectoral innovation flows, which we frame as technological interdependencies, in determining sectoral employment dynamics. This purpose is achieved through the construction of an indicator capturing the amount of R&D expenditures embodied in the backward linkages of industries. We aim to find out whether having a more integrated production in terms of requiring more technological inputs is related to a lower demand for workers within the sector. We refer to the literature on innovation-employment nexus, inter-sectoral knowledge spillovers and Global Value Chains, building upon structuralist and evolutionary theoretical considerations. We track the flows of embodied technological change between industries taking advantage of the notion of vertically integrated sectors. The relevance of this vertical technological dimension for determining employment dynamics is then tested on a panel data of European industries over the 2008-2014 period. Results show a statistically significant and negative employment impact of the degree of vertical integration in terms of acquisitions of R&D embodied inputs. Combining the role of demand, the double nature of innovation - as product and as process -, together with intersectoral linkages, this work shows that the dependence of a sector from innovation performed by other ones - a proxy for input embodied process innovations - exert a negative effect upon employment.
Keywords: F16; O14; O33; 330; Input-Output; Sectoral Interdependencies; Employment; Embodied Technological Change; Innovation Diffusion